2011
DOI: 10.1128/jcm.00355-11
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Diversity and Distribution of Orientia tsutsugamushi Causing Scrub Typhus in Thailand

Abstract: Scrub typhus, caused by antigenically disparate isolates of Orientia tsutsugamushi, is a widely distributed mite-borne human disease in the Asia Pacific region. Information regarding the heterogeneity of the immunodominant 56-kDa type-specific antigen (TSA) gene is crucial for the design and evaluation of scrub typhusspecific diagnostic assays and vaccines. Using indirect immunofluorescence assays (IFA) and PCR assays, O. tsutsugamushi was detected samples from rodents and patients with fever of unknown origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Multiple alignment and phylogenetic analysis demonstrated that the 4 O. tsutsugamushi isolates from Ban Pongyeang fell into 4 clusters. Sequences for 3 of the isolates clustered with Gilliam, LA, and TA, 3 genotypes that are commonly found in Southeast Asia ( 10 , 11 ); the sequence of the fourth isolate presented as a divergent distinct genotype (Figure 2). Most of the children were infected with a strain genetically similar to the LA cluster (Figure 2).…”
Section: The Studymentioning
confidence: 99%
“…Multiple alignment and phylogenetic analysis demonstrated that the 4 O. tsutsugamushi isolates from Ban Pongyeang fell into 4 clusters. Sequences for 3 of the isolates clustered with Gilliam, LA, and TA, 3 genotypes that are commonly found in Southeast Asia ( 10 , 11 ); the sequence of the fourth isolate presented as a divergent distinct genotype (Figure 2). Most of the children were infected with a strain genetically similar to the LA cluster (Figure 2).…”
Section: The Studymentioning
confidence: 99%
“…Recent studies have established the impact of scrub typhus and murine typhus as causes of acute febrile illness in Thailand (Blacksell et al 2008, Thitivichianlert et al 2009, Ruang-Areerate et al 2011) and adjacent countries (Phongmany et al 2006, Chheng et al 2013, Mayxay et al 2013, McGready et al 2014). Although pathogens like Orientia tsutsugamushi and Rickettsia typhi are well described, only limited evidence is available for other zoonotic pathogens contributing to the burden of undifferentiated febrile illness.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting genotypes exhibited much lower similarity to the prototype strains than previously described. 17,18 In the current study, we also use the 56-kDa TSA gene sequence (700 basepairs [bp]) to characterize O. tsutsugamushi from 12 naturally infected, laboratory-reared Leptotrombidium colonies (comprising three Leptotrombidium species: L. deliense, L. imphalum, and L. chiangraiensis) located at the Armed Forces Research Institute of Medical Sciences in Bangkok, Thailand (AFRIMS). As knowledge regarding the transmission dynamics of O. tsutsugamushi and chigger-host interactions is limited, we evaluated the degree to which the composition of O. tsutsugamushi genotype(s) found in an individual chigger is maintained in the rodent host post-infection.…”
Section: Introductionmentioning
confidence: 99%